Amino acid score of some products for younger school children nutrition - M. Vatan; V. Babienko (Journal of Education, Health and Sport, 2023)
Introduction. Wholesome nutrition is one of the most important factors in shaping a person's somatic and mental health. Eating habits are formed in childhood and consolidated in adulthood. They can also have an impact on the development of future chronic diseases, such as metabolic syndrome, type 2 diabetes, cardiovascular diseases. The purpose of the work is to evaluate the amino acid score of the main food products of children of primary school age.